Application of PCR in serum samples for diagnosis of paracoccidioidomycosis in the southern Bahia-Brazil. - Lucas Dias; Leila Falcão de Carvalho; Carla C Romano (Public Library of Science (PLoS), 2012)
Paracoccidioidomycosis (PCM) cannot always be diagnosed by conventional means such as direct examination of histopathology or clinical samples, and serological methods, used as an alternative, still have many cases of cross-reactivity. In this scenario, molecular techniques seem to arise as a rapid approach, specific and direct that could be used in the diagnosis of this mycosis. In this study we analyzed 76 serum samples from patients in southern Bahia suspected of having paracoccidioidomycosis using a conventional PCR with primers for the ITS1 ribosomal DNA of P. brasiliensis. Of these 76 patients, 5 were positive for PCM by double immunodiffusion and/or direct examination and histopathology. To test specificity of PCR, we used human DNA and three isolates of P. lutzii (1578, 01 and ED01). Additionally, we analyzed by serial dilutions of DNA the limit of detection of the assay. The test of PCR proved specific, as only a 144 bp fragment of the three isolates of P. lutzii and no human DNA was amplified. Detection limit was 1.1 pg/µL of DNA. Despite the high detection limit and specificity of PCR none of the 76 serum samples were found positive by PCR, but a biopsy specimen obtained from one of the patients with PCM was positive. These results, albeit limited, show that PCR is not effective in detecting DNA of P. brasiliensis or P. lutzii in serum, but could perhaps be used with other types of clinical samples, especially in those instances in which conventional methods fail.